Spirit possession in the central Himalayas - Krengel, Monika (Éditions de l’École des hautes études en sciences sociales, 1999)
In this paper I explore different arenas and aspects of spirit possession, as observed during fieldwork in Kumaon/Himalaya. The ritual is called jāgar. One aim of this paper is to demonstrate that spirit possession is a very complex institution, which is simultaneously concerned with a whole range of issues. I put forward the argument, that jāgars, although they appear due to actual problems, for example, illness of a person, are not just held for the purpose of healing, but provide a stage for active discourses on past, present and future affairs of the local society. A jāgar resembles a journey, for which an actual problem or symptom is just the starting point. The oracular communication with the divine (evil spirits and deities) leads to misdeeds that have no connection with the symptoms and deeds of the person suffering. I try to investigate the impact of divine justice, embodied in the voices of local deities, on society and persons, and its relation to the concept of responsibility and guilt.Ambivalences with regard to just and unjust, and the question if the right path has been taken to unfold the truth, make jāgars a medium where the divine messages are incorporated into worldly discourses and a process of argumentation. It will be shown that the power of the person has a strong gender bias, but that identity, power and responsibility are finally bound to territory and landed property.